2010
DOI: 10.1177/1096348010380598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance and Scale Characteristics of the Australian Restaurant Industry

Abstract: This article adopts a data envelopment analysis (DEA) bootstrap approach to measure the technical efficiency and scale properties of Australian restaurant operations. Four inputs and two outputs are used in the analysis, covering 105 restaurants. The results show that Australian restaurants incorporated in this study are operating at a low level of efficiency, with an average of around 46.17%. Inferences from the returns to scale are also in line with the efficiency results and indicate that most restaurants n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 28 publications
5
53
0
1
Order By: Relevance
“…Despite a bulk of prior research (e.g., Assaf et al, 2010;David et al, 2006;Geller and Heath, 1981;Hua et al, 2011;Madanoglu et al, 2008;Morey and Dittman, 2003;Parsa et al, 2005) in restaurant financial performance, a void still exists in the literature to address sustained financial performance. By examining a firm's capabilities from a benchmarking perspective, this study provides empirical evidence that critical firm capabilities can be identified and used to understand what can be done further for restaurant firms to achieve sustained financial performance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite a bulk of prior research (e.g., Assaf et al, 2010;David et al, 2006;Geller and Heath, 1981;Hua et al, 2011;Madanoglu et al, 2008;Morey and Dittman, 2003;Parsa et al, 2005) in restaurant financial performance, a void still exists in the literature to address sustained financial performance. By examining a firm's capabilities from a benchmarking perspective, this study provides empirical evidence that critical firm capabilities can be identified and used to understand what can be done further for restaurant firms to achieve sustained financial performance.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, how to achieve sustained financial performance emerges as a critical empirical question even more for the restaurant industry than for other industries which are less sensitive to economic conditions. Although a significant amount of attention has been paid to understanding restaurant performance or failure (e.g., Assaf et al, 2010;David et al, 2006;Geller and Heath, 1981;Hua et al, 2011;Madanoglu et al, 2008;Morey and Dittman, 2003;Parsa et al, 2005), prior studies have not yet addressed the issue of sustained restaurant financial performance, leaving a critical gap in the hospitality literature. Sustained financial performance may be defined as a financial performance pattern that exhibits value growth over a period of ten years (e.g., Roberts and Dowling, 2002) and three major theoretical perspectives have emerged in support of benchmarking firm capabilities to gain sustainable competitive advantages and better performance: (1) resource-based view (RBV) theory (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…With many surrounding businesses in the area where the study was conducted, even a training restaurant, where on average each guest pays over GBP 10 (approximately $US17) for a three-course menu, may be vulnerable to failing to provide an overall satisfying experience. A number of researchers have discussed the critical aspect of competition within the restaurant industry (e.g., Assaf, Deery and Jago, 2011;Horng et al, 2013;Maumbe, 2012). Hence the need for the training restaurant to avoid any form of complacency and maintain consistency in the elements currently perceived as satisfactory, while seeking to improve in others that, as in the case of some atmospheric elements, appear to be in need of improvement.…”
Section: Resultsmentioning
confidence: 99%
“…The internal characteristics include firm size or age (Assaf, Deery, and Jago 2009;Assaf and Cvelbar 2010), while external factors include the characteristics of the industry to which the firm belongs (Scherer and Ross 1990;Fernández, Montes, and Vázquez 1996).…”
Section: Literature Review On the Relationship Between Economic Profimentioning
confidence: 99%